2002
DOI: 10.1074/jbc.m111514200
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome-inactivating and Adenine Polynucleotide Glycosylase Activities in Mirabilis jalapa L. Tissues

Abstract: Several tissues of Mirabilis jalapa L. (Nyctaginaceae)were assayed for inhibition of translation by a rabbit reticulocyte lysate (as a signal of ribosome-inactivating activity) and for adenine DNA glycosylase activity, activities that are both due to the presence of a class of enzymes called ribosome-inactivating proteins (RIPs), currently classified as rRNA N-glycosylases (EC 3.2.2.22). These activities were highest in seed; intermediate in flower bud, immature seed, sepal ؉ gynoecium, leaf, and root; and ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 33 publications
4
37
0
1
Order By: Relevance
“…Type 1 RIPs and the A subunit of type 2 RIPs is an RNA Nglycosidase that cleaves adenine molecules from ribosomal RNA, thus inactivating the ribosome in an irreversible manner. In addition, they remove adenine residues from the DNA (Barbieri et al, 2000;Bolognesi et al, 2002).…”
Section: Immunotoxinsmentioning
confidence: 99%
“…Type 1 RIPs and the A subunit of type 2 RIPs is an RNA Nglycosidase that cleaves adenine molecules from ribosomal RNA, thus inactivating the ribosome in an irreversible manner. In addition, they remove adenine residues from the DNA (Barbieri et al, 2000;Bolognesi et al, 2002).…”
Section: Immunotoxinsmentioning
confidence: 99%
“…Saporin-S6 was revealed by incubation overnight with a rabbit anti-saporin-S6 serum. 15 Detection was carried out with a horseradish peroxidase-conjugated goat anti-(rabbit IgG)Ig and with 4-chloro-naphtol (Sigma).…”
Section: Immunotoxinsmentioning
confidence: 99%
“…They also remove adenine residues from DNA, hence the denomination of adenine polynucleotide glycosylase proposed for RIPs. 15 To date, several clinical trials have been conducted with immunotoxins, and some of them are still ongoing, to evaluate their antitumor efficacy. The response rates observed in phase I/II trials have often been higher than those reported for some of the conventional antiblastic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Depurination of the S/R loop prevents binding of elongation factor 2 to the ribosome, and results in protein synthesis inhibition (Stirpe et al 1992). Apart from the depurination of rRNA, some RIPs exhibit the ability to depurinate DNA, poly(A) and viral RNA (Barbieri et al 1994(Barbieri et al , 1997Bolognesi et al 2002). Many RIPs possess antimicrobial and antiviral activities.…”
Section: Introductionmentioning
confidence: 99%